VC’S graduation address at the 16th congregation of MSU- 25th November 2016 - Muzvidziwa, Victor N. (Midlands State University, 2017)
A speech by Professor Victor Ngonidzashe Muzvidziwa, Acting-Vice Chancellor, Midlands State University, Zimbabwe